PENGEMBANGAN MODUL BERBASIS INSTAD PADA MATERI SISTEM PEREDARAN DARAH UNTUK SISWA KELAS XI DI MAN 1 METRO - Ayu Eka Sari; Handoko Santoso; Agil Lepiyanto (EDUBIOLOCK, 2020)
The development of this module is motivated by several difficulties experienced by students in the learning process. Some of these difficulties are that students do not understand the teaching materials that used, besides that, students are also less interested in teaching materials that used in the learning process. The purpose of this research is to produce products in the form of modules that are suitable for use, and overcome the difficulties experienced by students. The type of development research that used in this study is the 4D model suggested by Thiagarajan, Semmel and Semmel (1974). The 4D model has 4 stages namely Define, Design, Develop and Disseminate, but this research is only carried out until the Develop stage. This developed product has been validated by experts for 2 times. The results obtained from the first stage of validation were design and language experts got the score of 81% with the criteria of "Good", material experts were 81.84% with the criteria of "Good". The results of the second stage of validation are design and language experts and got the result of 88.42% with the criteria "Very Good", 85.63% point of material experts with the criteria "Very Good" and small group trials obtained results of 83.83% with the criteria "Good". Based on the results of expert validation and small group trials, the product in the form of modules developed has been appropriate for students to use without revision.